Customer recognition and competition - Oz Shy; Rune Stenbacka (Federal Reserve Bank of Boston, 2011)
We introduce three types of consumer recognition: identity recognition, asymmetric preference recognition, and symmetric preference recognition. We characterize price equilibria and compare profits, consumer surplus, and total welfare. Asymmetric preference recognition enhances profits compared with identity recognition, but firms have no incentive to exchange information regarding customer-specific preferences (symmetric preference recognition). Consumers would benefit from a policy panning information exchange regarding individual consumer preferences. Our welfare analysis shows that the gains to firms from uniform pricing (no recognition) are larger than the associated harm to consumers, regardless of which regime of customer recognition serves as the basis for comparison.
Keywords: D4; D82; L1; L4; 330; customer recognition; price discrimination; behavior-based pricing; Betriebliche Preispolitik; Preisdifferenzierung; Konsumentenverhalten; Zielgruppe; Asymmetrische Information; Marktforschung